Silica-Based Chemical Gel for Decontamination of Radionuclides - Jung, Chong-Hun; Choi, Byung-Sun; Moon, Jei-Kwon; Won, Hui-Jun; Lee, Kune-Woo; Kim, Chang-Ki (Asian Journal of Chemistry, 2012)
The appropriate combination of viscosifier and coviscosifier is a very important factor in the control of the viscosity and adhesion properties of chemical decontamination gels. A chemical decontamination gel was prepared by adding gelling agents composed of a pyro Si viscosifier and PEG-based non-ionic coviscosifier (tripropylene glycol butyl ether and tripropylene glycol dodecyl ether) into a Ce(IV) solution stabilized in concentrated nitric acid. The decontamination and rheological behaviours, along with the drying behaviours of a chemical gel for SUS 304 metallic surfaces contaminated with Co and Cs radionuclides were investigated. A chemical gel containing a 0.5 wt % tripropylene glycol dodecyl ether coviscosifier was more effective in terms of the rheological and drying-detachment properties and the radionucleide decontamination effectiveness in particular, compared to tripropylene glycol butyl ether.